VINTGES, Karen. A New Dawn for the Second Sex: Women's Freedom Practices in World Perspective - Santos, Magda Guadalupe dos (Virtuajus, 2017)
Review of the book A New Dawn for the Second Sex: Women’s Freedom Practices in World Perspective of Karen Vintges, a University Lecturer in Political and Social Philosophy in the Department of Philosophy at the University of Amsterdam.